Los créditos de consumo de una entidad bancaria y su efecto en la economía de los clientes en el periodo 2001-2004 en la ciudad de Tarapoto - Lorena valles Document (2007)
The present "Thesis the Credits of Consumption of a Banking Organization and their Effects in the Economy of the Clients in Period 2001 - 2004" respond to the problem is the credits of consumption granted by the banking organization a factor of improvement of the economy of the clients of the city of Tarapoto?, in merit to which a positive hypothesis and another refusal consider, those that by means of the comparative descriptive design are resisted. Part of a theoretical conceptual trame about the bank and is distinguished of way makes specific concerning the types of credits that the bank grants specifically and, the referring thing to the consumption credits. The used methodologic process has allowed to present/display the data of the survey as well as to arrive at its interpretation, by means of which it demonstrates that the consumption credits have been a factor of improvement in the economy of the clients, in the analyzed period, which if it has benefitted to the bank in himself, the one that is rigorous in the selection of its portfolio of clients. Finally, one infers the conclusions and made recommendations of the study